The supervisory role of the central bank in the protection of commercial banks: An applied research in the Economy Bank for Investment and Finance (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Represents a supervisory and oversight role of the Central Bank  towards finding a sober banking sector, as the procedures , regulations and laws that the Central Bank insists on its implementation with the utmost precision, and that was to protect depositors and shareholders' class basis rights, but it is in the interest of the bank in the end, as it seeks to improve the performance of commercial banks and vaccinated against falling into the blunders, they also contribute to building a sober and stable banking sector and security contributes to the welfare and employment optimization of economic resources, and treatment of research (and the presence of banks decline in financial performance, according to financial performance indicators to the level Which it has become difficult for them to comply with the requirements commercial banking operations, which may be reflected negatively on the banking system in general.And research started from the premise that: contributes to the central bank contributes to (in turn, the supervisory and regulatory) in dealing with the case of default of commercial banks in Iraq by taking appropriate measures, whether before placing the bank under guardianship or after.The researcher reached a set of conclusions was the most prominent: Delay by the Central Bank of Iraq's decision to custody of the banks put (sample), although the financial indicators available for the friendly showing a significant financial risk faced by banks, causing the delay in the increase of loss and the aggravation of the crisis, which is exposed.It is then recommended to search a set of recommendations, the most important (the need to expedite the issuance of the Iraqi Central Bank's decision to impose custody of the bank in the event of discovery of the onset of the financial crisis of the bank in order to remedy the situation before exacerbations.